Treatment of gas-containing lumbar disc cysts via a combination of posterior and extraforaminal approaches in arthroscopic-assisted uni-portal spine surgery: a case report and literature review - Guijun Zhang; Lei Ren; En Song; Shengjun Shen (BMC Musculoskeletal Disorders)
Abstract Background Gas-containing lumbar disc cysts (LDCs) are a rare spinal pathology that frequently manifest as sciatica and exhibit clinical features akin to those observed in lumbar disc herniation. Their radiological presentation closely resembles that of synovial cysts, which can result in misdiagnosis, and their development is hypothesized to be associated with the ‘vacuum phenomenon’ observed in degenerative discs. Previous literature has documented various treatment modalities for disc cysts. In this report, we successfully excised the lesion using a combination of a posterior approach and an extraforaminal approach, facilitated by arthroscopy-assisted uniportal spinal surgery. Case presentation An 85-year-old male patient developed persistent low back pain one month prior, accompanied by radiating discomfort in both lower extremities, predominantly on the right. Lumbar magnetic resonance imaging (MRI) and computed tomography (CT) scans revealed hypertrophy of the ligamentum flavum at the posterior margin of the L4/5 level, accompanied by spinal canal stenosis, and a gas-containing cyst on the right side extending into the extraforaminal region, which resulted in neural compression and functional impairment. The patient was treated using the AUSS technique. During the procedure, a unilateral posterior approach was initially employed to achieve unilateral laminotomy for bilateral decompression (ULBD) and excision of the intracanal cyst, followed by resection of the cysts in the foraminal and extraforaminal regions via an extraforaminal approach. Conclusion Although gas-containing lumbar disc cysts are rare, the combined dual-approach AUSS technique has yielded favorable clinical outcomes. Postoperatively, the patient experienced marked improvement in lower limb pain and numbness; CT imaging confirmed complete cyst resection and adequate decompression of the dural sac and nerve roots.